Effects of wheat gluten modified by deamidation-heating with three different acids on the microstructure of model oil-in-water emulsion and rheological–physical property of ice cream. (February 2019) - He, Wenmeng; Zhao, Wei; Yang, Ruijin
Abstract: A by-product of wheat wet processing, wheat gluten (WG) exhibits low solubility, which restricts its application as an emulsifier and a stabilizer in oil-in-water emulsions. WG modified by acetic acid, tartaric acid, and citric acid deamidation combined with heat treatment, can improve the solubility, surface hydrophobicity, as well as the emulsifying and foaming properties of the modified WGs (MWGs). The principal component analysis suggested the emulsifying and foaming properties of the citric acid-deamidation-heating WG (CDWG) were the highest. High-molecular-weight proteins and crosslinking of proteins were observed in the MWGs by sodium dodecyl sulfate–polyacrylamide gel electrophoresis. Scanning electron microscopy results showed that the granules of the MWGs were more regular than those of WG. Model oil-in-water emulsions stabilized by MWGs could prevent oil droplets from coalescence, and the emulsion stabilized by CDWG was more stable and homogenous than the other emulsions. Positive correlations were observed between the substitution ratio of skim milk powder with MWGs and viscosity, as well as the G′ and G″ values of the ice cream mixes. All the mixes exhibited the non-Newtonian shear thinning flow behavior. Partial least squares discriminant analysis of the physicochemical and rheological properties of the ice cream samples indicated that C2 possessed the appropriate rheological properties and physical characteristics that could be used by a prototype for the further development of ice cream prepared using CDWG. Graphical abstract: Image 1 Highlights: Wheat gluten (WG) was treated with acetic acid, tartaric acid, and citric acid deamidation combined with heating to improve functional properties of WG. The principal component analysis suggested the emulsifying and foaming properties of the citric acid-deamidation-heating WG (CDWG) were the highest. Model oil-in-water emulsions stabilized by the three acid-deamidation-heating WGs prevented flocculation and coalescence of emulsions. Oil-in-water emulsions stabilized by CDWG showed increased stability. The partial least squares discriminant analysis concluded that C2 ice cream could be used as a prototype for the further development of ice cream.